The Critical Turn in Tourism Studies : Creating an Academy of Hope. - Ateljevic, Irena (Advances in Tourism., 2011)
In today's increasingly complex tourism environment, decision-making requires a rounded, well-informed view of the whole. Critical distance should be encouraged, consultation and intellectual rigour should be the norm amongst managers and there needs to be a radical shift in our approach to educating future tourism and hospitality managers and researchers. This second edition intends to move the debate forward by exploring how critical tourism inquiry can make a difference in the world, linking tourism education driven by the values of empowerment, partnership and ethics to policy and practice.